THE IMPLEMENTATION OF SELF-ASSESSMENT IN TEACHING READING COMPREHENSION ON NARRATIVE TEXT - Sari Selutan, Ira Permata; Sutapa, Gatot; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purposes of this research are to find out the effectiveness and how effective the implementation of self-assessment in teaching reading comprehension on narrative text to the tenth grade students of SMA Negeri 7 Pontianak in academic year 2014/2015. In this research, the writer used pre-experimental research and the sample was class X IIS 1 which consists of 33 students. The research found that the students in the school need an effective assessment which might help them engage in the learning process and give them feedback that hence improved future learning. The result of this research shows that self-assessment helps students in reading comprehension on narrative text which is represented by the t-compution is 28.39 with the effect size is 16.39 or categorized as strong effect. It indicates that the implementation of self-assessment is effective in teaching reading on narrative text. Â  Keywords: Self-Assessment, Reading Comprehension, Narrative Text Abstrak: Penelitian ini bertujuan untuk mengetahui keefektifan dan tingkat efektifitas dari penerapan self-assessment dalam pengajaran komprehensi membaca pada teks narrative terhadap siswa kelas 10 SMA Negeri 7 Pontianak tahun ajaran 2014/2015. Penilitian ini dilakukan dengan metode pre-eksperimen dan sampel penilitian adalah kelas X IIS 1 yang terdiri atas 33 siswa. Dari penilitian yang dilakukan ditemukan bahwa siswa di sekolah tersebut memerlukan cara penilaian yang efektif untuk membantu mereka terlibat dalam proses belajar and memperoleh umpan balik untuk perkembangan pembelajaran. Hasil penelitian ini menunjukan bahwa self-assessmentÂ membatu komprehensi membaca siswa pada teks narrative yang dibuktikan pada t-compution 28.39 dengan tingkat efektifitas 16.39 atau dikategorikan memiliki efek yang kuat. Hal ini menandakan bahwa penerapan self-assessment efektif dalam pengajaran komprehensi membaca pada teks narrative. Â  Kata Kunci: Self-Assessment, Komprehensi Membaca, Teks Narrative